Development of a Decision Support Algorithm in Emergency Situations at Telecommunication Objects - Misliddinovich, Qodirov Fazliddin; Munirovna, Abdullayeva Surayyo; Anatolyevna, Borisova Elena; Yuryevna, Amurova Natalya (European Journal of Life Safety and Stability (2660-9630), 2022)
The papers developed an algorithm for decision support in emergency situations at telecommunications facilities based on 3D geoinformation modeling technologies, which make it possible to increase the efficiency of decisions made in the field of prevention and elimination of nuclear power plants at production facilities due to the visibility of the analyzed information. The articles set and achieved the goal of developing methods and algorithms for processing information about production facilities based on 3D geoinformation modeling technologies to improve the efficiency of the decision support process in emergency situations.